Trends in environmental tobacco smoke restrictions in the home in Victoria, Australia. Issue 3 (1st September 1999) - Borland, Ron; Mullins, Robyn; Trotter, Lisa; White, Victoria
Abstract : OBJECTIVE: To assess the extent to which smokers and non-smokers in Victoria, Australia attempt to keep their homes smoke free and to determine whether the proportion of people attempting to do so has changed over time. METHODS: Face to face surveys conducted in Victoria each year from 1989 to 1997. PARTICIPANTS: Approximately 2500 randomly selected adults each year. MAIN OUTCOME MEASURES: Proportion of respondents who discourage their visitors from smoking; proportion of smokers who always smoke outside their own homes; behaviour of smokers when they are around children. Changes in each of these measures over time. RESULTS: Reports of visitors being discouraged from smoking rose from 27% in 1989 to 53% in 1997. Smokers who reported always smoking outside the home rose from 20% in 1995 to 28% in 1997. Not smoking in the presence of children rose from 14% in 1989 to 33% in 1996. Indoor restrictions on smoking were associated with the presence of children in the household and even more strongly with the presence of non-smoking adults. People who worked in places where smoking was totally banned were more likely to ask their visitors not to smoke than those who worked where smoking was allowed. CONCLUSIONS: The results indicate a strong move towards homes and towards protecting children from smoke. Efforts to support and facilitate this social change should be further encouraged.